2021
DOI: 10.3390/math9111275
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Mixed Convective Flow over a Moving Yawed Cylinder Driven by Buoyancy

Abstract: The fluid flow over a yawed cylinder is useful in understanding practical significance for undersea applications, for example, managing transference and/or separation of the boundary layer above submerged blocks and in suppressing recirculating bubbles. The present analysis examines nonlinear mixed convection flow past a moving yawed cylinder with diffusion of liquid hydrogen. The coupled nonlinear control relations and the border restrictions pertinent to the present flow problem are nondimensionalized by usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…Finite Fourier sine transform, Laplace, and fractional techniques have been utilized to the governing equations for exhibiting typical and rheological properties of the problem. Although the studies on heat and transfer analysis can be continue yet the relevant studies can be observed therein in categorical format as heat transfer via analytical approaches [16][17][18][19][20][21][22][23], heat transfer via numerical approaches [24][25][26][27][28][29], heat transfer via fractional calculus approaches [30][31][32][33], and heat transfer via multi-dimensional approaches [34][35][36][37]. Motivating by the above consideration, the main theme of this manuscript is to have the significance of convective heating and variable heat source on Azimuthal oscillatory MHD convective flows developed in a cylindrical Darcy-Forchheimer porous medium filled by a radiating second-grade fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The nonsimilar approach was used to reduce the governing equations and boundary constraints. In addition, the quasilinearization approach and implicit finite difference schemes are used to solve these equations 41–43 . The numerical results are validated with the existing literature and found that they are in excellent agreement.…”
Section: Introductionmentioning
confidence: 77%
“…neighboring liquid (i.e., T S > T ∞ ). The equations representing the fluid flow variations are as follows [20][21][22][23][24]29,37,43,45,46 :…”
Section: Mathematical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the current method accounts for nonlinear density temperature concentration (NDTC) differences in the buoyancy force. Vajravelu and Sastri, 17 Bhargava and Agarwal, 18 Mandal and Mukhopadhyay, 19 Khan et al, 20 and Patil et al 21 are only a few of the researchers who have looked into quadratic convection. Cross‐diffusion pertains to the combined impact of Soret and Dufour on heat and mass transport.…”
Section: Introductionmentioning
confidence: 99%